Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 month ago

How to find the vertical asymptote using limits of f(x)= (2x+3)/sqrt(x^2-2x-3)?

2 Answers

Relevance
  • Favorite Answer

    x^2 - 2x - 3 = 0

    x = (2 +/- sqrt(4 + 12)) / 2

    x = (2 +/- 4) / 2

    x = 1 +/- 2

    x = -1 , 3

    When x = -1 and when x = 3, the function is undefined.  No need for limits.

  • alex
    Lv 7
    1 month ago

    x^2-2x-3=(x+1)(x-3)=0---> x= ...

Still have questions? Get your answers by asking now.